(The Impact of Quality of Work Life on Human Resources Management Practices (A Field Study on the Administrative staff of the Armed Forces Hospital in the Southern Saudi Arabia - Al Qurashi, Susan Mohammed; Qahtani, Samia Muthckar (Journal of Economic, Administrative and Legal Sciences, 2018)
The current search aimed to recognize the reality of the quality of work life and human resources management practices in Armed Forces Hospital in the Southern Saudi Arabia, and also determine the relationships between the dimensions of the quality of work life including: (moral conditions of work, job characteristics, compensations and benefits, work group, the method of the leader in supervision and participation in decisions) and human resources practices (development and training, salaries and rewards, performance assessment and attracting and selecting), and finally, to investigate that there are statistical significant differences around the responses of the study sample according to the variables of (gender, qualification, career level, age, experience and nationality). The population of the study included (767) administrative employees in Armed Forces Hospital in the Southern of Saudi Arabia Kingdom during the period of the field study in (2016/2017). A number of (262) questionnaires were distributed to a randomized sample from the population of the study, and the researcher returned back (233) questionnaires that were valid and analyzable. The researcher used the descriptive analytical approach as a search method. The researcher depended on establishment and development of the questionnaire after reviewed study of (almaghrabi,2004). Then analyzed using SPSS. Cronbach was verified (82.0 - 89.0) The search concluded to several results, the most important are: there is a high quality in the work life of the administrative employees in Armed Forces Hospital and the highest quality was in moral conditions of work(sma= 4.23), while the lowest quality was in participation in decisions(sma= 3.88). The Armed Forces Hospital has a high degree in human resources management, as the practice of performance assessment was considered the most interested(sma=4.24), while salaries and rewards were the lowest interesting(sma= 3.83). There was positive direct impact of the quality of work life on human resources management practices in Armed Forces Hospital in the southern, and salaries and rewards were considered the most influential on human resources management. (t=7.730) The researcher recommended with many recommendations, the most important are: give the opportunity to the administrator in Armed Forces Hospital in the southern with discretionary power in emergency cases that he encounters in the hospital in a proper way for the case. Encourage administrators to work as one team and express their feelings and suggestions towards administrators freely. There is a need to conduct practical workshops by different departments of organizations to develop and activate the quality of work life on human resources management practices.